The Alteration of Irisin—Brain-Derived Neurotrophic Factor Axis Parallels Severity of Distress Disorder in Bronchial Asthma Patients - Szilasi, Magdolna E.; Pak, Krisztian; Kardos, Laszlo; Varga, Viktoria E.; Seres, Ildiko; Mikaczo, Angela; Fodor, Andrea; Szilasi, Maria; Tajti, Gabor; Papp, Csaba; Gesztelyi, Rudolf; Zsuga, Judit (Frontiers in Neuroscience, 2017)
Distress disorder (a collective term for generalized anxiety disorder and major depressive disorder) is a well-known co-morbidity of bronchial asthma. The irisin – brain-derived neurotrophic factor (BDNF) axis is a pathway that influences several neurobehavioral mechanisms involved in the pathogenesis of distress disorder. Thus, the aim of the present study was to quantify the serum irisin and BDNF concentrations in order to investigate the possible link between the irisin/BDNF axis and distress disorder in an asthma patient cohort. Data of 167 therapy-controlled asthma patients were analyzed. Demographic, anthropometric and anamnestic data were collected, routine laboratory parameters supplemented with serum irisin and BDNF levels were determined, pulmonary function test was performed using whole-body plethysmography, and quality of life was quantified by means of the St. George's Respiratory Questionnaire (SGRQ). Correlation analysis as well as simple and multiple linear regression were used to assess the relationship between the irisin level and the Impacts score of SGRQ, which latter is indicative of the presence and severity of distress disorder. We have found a significant, positive linear relationship between the Impacts score and the reciprocal of irisin level. This association was stronger in patients whose BDNF level was higher, and it was weaker (and statistically non-significant) in patients whose BDNF level was lower. Our results indicate that higher serum irisin level together with higher serum BDNF level are associated with milder (or no) distress disorder. This finding suggests that alteration of the irisin/BDNF axis influences the presence and severity of distress disorder in asthma patients.